OC-032 A New Validated whole Gut Transit Time (WGTT) Measurement using Magnetic Resonance Imaging (Mri-Wgtt) Technique. (4th June 2013) - Lam, C; Chaddock, G; Hoad, C; Costigan, C; Cox, E; Marciani, L; Gowland, P; Spiller, R
Abstract : Introduction: Disorders of gut transit are very common in gastroenterology clinics. Objective assessment may be useful for targeting and monitoring treatment. Current scintigraphic or radio-opaque marker techniques involve undesirable ionising radiation. Aims: To validate a new MRI method for measuring WGTT against the current gold standard in which 20 radio-opaque markers (ROMs) are ingested per day on 3 consecutive days and the number retained assessed from a single abdominal x-ray on day 4. To assess reproducibility of MRI-WGTT. Methods: 20 healthy volunteers (HV) ages 21–70 (12 males and 8 females) participated in the study involving 2 visits a week apart (test-retest). On each visit, each HV underwent 2 tests: (A) MRI-WGTT test for which HV swallow 5 pills, each filled with a MRI contrast agent diluted with water, 24 hours before undergoing MRI scans which precisely locate the pills in the colon. Transit of the markers was assessed by scoring each pill from its position in the colon (7 = small bowel, 6 = lower ascending 5 = upper AC, 4 = right transverse (TC), 3 = left TC, 2 = descending, 1 = rectosigmoid, 0 = expelled) and calculating an average score (Transit score TS) using an algorithm which gives a weighting inversely related to the distance from the median. (B) ROM test: the number of ROM was counted and multiplied by 1.2 to give a WGTT in hours. Spearman's correlation was used to assess the correlation between the two measurements and intra-class correlation coefficient (ICC) was used to assess the variability of each test when repeated twice. Results: The MRI images provided excellent 3D spatial resolution, allowing the gut to be viewed from all angles, hence allowing accurate location of the pills within the colon especially the sigmoid region (Figure 1 ). WGTT using ROM was median (SD), 27.6 (20.8) and TS was 0.9 (0.8). WGTT using ROM and TS were well correlated, Spearman's r = 0.85, p < 0.01. Using this we converted TS to MRI-WGTT in hours. Mean calculated MRI-WGTT was 27.6 (24.7) hours. The mean absolute difference in the MRI-WGTT on 2 separate visits was 15.3 hours (SD, 15.8) with an ICC of 0.62 (p < 0.01). The mean absolute difference in the WGTT for ROMS on 2 separate visits was 11.3 hours (SD, 9.7) with and ICC of 0.69 (p < 0.01). Conclusion: MRI-WGTT correlated well with the gold standard ROM WGTT but was more convenient, involving only one day of marker ingestion and no exposure to ionising radiation. This technique could be implemented easily in most NHS hospitals. Funded by: Medical Research Council and NIHR UK. Disclosure of Interest: None Declared